2011
DOI: 10.1038/ejhg.2011.187
|View full text |Cite
|
Sign up to set email alerts
|

Unique and atypical deletions in Prader–Willi syndrome reveal distinct phenotypes

Abstract: Prader-Willi syndrome (PWS) is a multisystem, contiguous gene disorder caused by an absence of paternally expressed genes within the 15q11.2-q13 region via one of the three main genetic mechanisms: deletion of the paternally inherited 15q11.2-q13 region, maternal uniparental disomy and imprinting defect. The deletion class is typically subdivided into Type 1 and Type 2 based on their proximal breakpoints (BP1-BP3 and BP2-BP3, respectively). Despite PWS being a well-characterized genetic disorder the role of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 35 publications
(49 reference statements)
1
66
0
3
Order By: Relevance
“…Of these, the smallest deletions that give rise to classical PWS phenotypic features are in a region that encompasses the small nucleolar RNA (snoRNA) SNORD116 (6)(7)(8)(9)(10). The analogue of this gene in mice, Snord116, is present in the corresponding murine PWS critical region, conserved on chromosome 7 (11,12).…”
Section: Original Articlementioning
confidence: 99%
“…Of these, the smallest deletions that give rise to classical PWS phenotypic features are in a region that encompasses the small nucleolar RNA (snoRNA) SNORD116 (6)(7)(8)(9)(10). The analogue of this gene in mice, Snord116, is present in the corresponding murine PWS critical region, conserved on chromosome 7 (11,12).…”
Section: Original Articlementioning
confidence: 99%
“…4,5 However, so far, all reported clinical cases of limited deletion of the SNORD116 cluster associated with PWS have also involved adjacent genes: SNURF-SNRPN or SNORD115. [6][7][8][9] We report the first case of a patient with the highly typical features of PWS who presented a restricted deletion of the SNORD116 region which did not affect the expression of SNURF-SNRPN and did not delete any portion of the SNORD115 locus. …”
mentioning
confidence: 95%
“…Based on these results, no significance differences were observed between the obese and nonobese groups. Kim et al (2012) used a different approach to measure the SNRPN methylation in a group of 80 subjects with early-onset morbid obesity; although the results of their study showed no statistically significant differences, the mean methylation in exon 1 of SNPRN (0.54 ± 00.6) did not differ from the mean methylation level seen in the control group of four subjects (0.55 ± 00.7). These results also suggest that the DNA methylation profile of SNRPN (in blood) does not correlate to the BMI (Kim et al, 2012).…”
Section: Discussionmentioning
confidence: 92%